2008
DOI: 10.1021/es802270t
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmia Is the Primary Response of Embryonic Pacific Herring (Clupea pallasi) Exposed to Crude Oil during Weathering

Abstract: Teleost embryos develop a syndrome characterized by edema when exposed to water that weathers substrates contaminated with crude oil. Previous studies using zebrafish demonstrated that crude oil exposure causes cardiogenic edema, and that the most abundant polycyclic aromatic hydrocarbons (PAHs) in weathered crude oils (tricyclic fluorenes, dibenzothiophenes, and phenanthrenes) are cardiotoxic, causing arrhythmia through a pathway that does not require activation of the aryl hydrocarbon receptor (AHR). We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
163
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 214 publications
(178 citation statements)
references
References 49 publications
14
163
0
1
Order By: Relevance
“…Oil exposure studies using zebrafish embryos demonstrated a heart failure syndrome that is lethal to larvae (13,14), findings that were validated in Pacific herring (15). As oil weathers, the proportional composition of dissolved-phase PAHs becomes dominated by the tricyclic fluorenes, dibenzothiophenes, and phenanthrenes (5,6,16), which were shown to be directly cardiotoxic (13,14).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Oil exposure studies using zebrafish embryos demonstrated a heart failure syndrome that is lethal to larvae (13,14), findings that were validated in Pacific herring (15). As oil weathers, the proportional composition of dissolved-phase PAHs becomes dominated by the tricyclic fluorenes, dibenzothiophenes, and phenanthrenes (5,6,16), which were shown to be directly cardiotoxic (13,14).…”
mentioning
confidence: 83%
“…As oil weathers, the proportional composition of dissolved-phase PAHs becomes dominated by the tricyclic fluorenes, dibenzothiophenes, and phenanthrenes (5,6,16), which were shown to be directly cardiotoxic (13,14). In herring embryos, cardiotoxicity occurred at tricyclic PAH concentrations in the tissue as low as 0.8 μmol/kg (150 ppb) wet weight, indicating a specific, high-affinity cellular target (15). Individual nonalkylated tricyclic PAHs caused atrioventricular conduction arrhythmias indistinguishable from those caused by drugs known to block potassium channels required for the repolarization phase of cardiac action potentials (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that these more abundant chemicals in crude oil target the heart and can cause heart failure in developing fish embryos (Incardona et al, 2004(Incardona et al, , 2005(Incardona et al, , 2009; see figure in box). This implies that most of the conventional tools for assessing oil exposure have limited usefulness for understanding effects on fish at vulnerable early life stages.…”
Section: Impact and Implications For Exposure Sciencementioning
confidence: 99%
“…More recent studies have built on these findings, with the goal of further sorting out which specific chemicals in complex oil mixtures are causing this early-life-stage toxicity in fish (Incardona et al, 2004(Incardona et al, , 2005(Incardona et al, , 2009). This more refined understanding is needed to develop next-generation biomarkers for oil exposure and to more accurately estimate the potential decline and recovery of fish populations that spawn in future spill zones.…”
Section: Introductionmentioning
confidence: 99%